Retracted article: Modelling of freight flows that consist of multiple products transported by different modes of transport in a multimodal network - Vasiliauskas, Aidas V. (Transport, 2002)
Freight flows which consist of multiple products transported by different modes of transport in a multimodal network get more and more attention in recent years. In this article a model for modelling flows of multiple products in the multimodal network is presented. The multimodal aspect of considered transport system is accounted by the chosen means of network representation. The multiproduct aspect is estimated by the solution procedure which is a GaussSeidel- Linear Approximation Algorithm. The article is closely connected with the following topics: • the representation of the network chosen for the reflection of transportation and transfer operations; • the formulation of a multimode multiproduct model; • the analysis of average and marginal cost functions; • the development of the solution algorithm; • the development of the algorithm used to compute the shortest path. View retraction statement: Statement of retraction First Published Online: 19 Dec 2011